Penguatan kedisplinan siswa pesisir di sekolah berbasis pesantren melalui pendekatan integratif humanistik - Moh. Ubaidyllah; Moh. Ulum (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
The issue of student discipline in coastal areas has become an educational challenge due to the flexible social characteristics of the community and a lack of time orientation. This qualitative case study aims to analyze the social characteristics of coastal students, identify the forms and causes of low discipline, and examine the implementation of a humanistic integrative approach in fostering discipline at MA Syarief Hidayatullah Pondok Kelor Paiton Probolinggo. Data was collected through observation, in-depth interviews, and documentation, then analyzed thematically. The results show that low discipline is reflected in tardiness, non-compliance with rules, and poor time management, influenced by the coastal family environment culture. However, applying a humanistic integrative approach through persuasive dialogue, empathy, role modeling, and guidance can encourage the intrinsic internalization of discipline values. The study concludes that fostering student discipline Coastal activities are more effective if carried out in a contextual, humanistic way, and are focused on strengthening ongoing personal awareness.